Data from: Microevolutionary selection dynamics acting on immune genes of the green veined white butterfly, Pieris napi ... - Keehnen, Naomi L.P.; Hill, Jason; Nylin, Sören; Wheat, Christopher W. (Dryad, 2018)
Insects rely on their innate immune system to successfully mediate complex interactions with their microbiota, as well as the microbes present in the environment. Previous work has shown that components of the canonical immune gene repertoire evolve rapidly and have evolutionary characteristics originating from interactions with fast-evolving microorganisms. Although these interactions are likely to vary among populations, there is a poor understanding of the microevolutionary dynamics of immune genes, especially in non-Dipteran insects. Here we use the full set of canonical insect immune genes to investigate microevolutionary dynamics acting on these genes between and among populations by comparing three allopatric populations of the Green Veined White butterfly, Pieris napi (Lepidoptera, Pieridae). Immune genes showed increased genetic diversity compared to genes from the rest of the genome and various functional categories exhibited different types of signatures of selection, at different evolutionary ... : Piebra_SP_k55b2000_MESPAnapiDraft genome of Pieris brassicae, scaffolded using MESPA.Pool-Seq libraries of the 3 P. napi populationsPool-Seq libraries of Spain: Aiguamolls, Sweden: Abisko, and Sweden: Kullaberg. Stored as NCBI bioproject PRJNA449143.command line scriptBioinformatics commands used to analyse the data.commandline.txtPnapi_FstEach row represents FST per base pair for all informative sites.Pnapi_TajD_piEach row represents pi and Tajima's D per gene, for all immune genes in the assembly.MK_gene_alignmentsMK gene alignments for significant genes. This is a zipped archive containing fasta files. ...